2006
DOI: 10.1177/0013916505281575
|View full text |Cite
|
Sign up to set email alerts
|

Design Issues in Hospitals

Abstract: Adolescents are underrepresented in the research on health care design. This qualitative study examined the preferences of 54 male and 46 female junior high school students, aged 12 to 14, regarding the physical design and visiting policies of hospitals. Participants compared and rated color photos of hallways and lobbies for units with adult-oriented decoration versus child-oriented decoration and answer questions about such issues as privacy, amenities, entertainment, and visiting hours policy. Responses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In Blumberg and Devlin's (2006) study, they observed that the needs of a sick child are quite different from those of adults, and to meet those needs, "the design of pediatric therapeutic settings differs greatly from those in adult or general care facilities" (p. 296). They too made use of a survey to ascertain the preferences of adolescents, should they require hospitalization.…”
Section: The Adolescentmentioning
confidence: 99%
“…In Blumberg and Devlin's (2006) study, they observed that the needs of a sick child are quite different from those of adults, and to meet those needs, "the design of pediatric therapeutic settings differs greatly from those in adult or general care facilities" (p. 296). They too made use of a survey to ascertain the preferences of adolescents, should they require hospitalization.…”
Section: The Adolescentmentioning
confidence: 99%
“…Specifically, inpatients' well-being when recovering from surgery may be increased if the hospital room offers adequate physical conditions that meet their needs and that can be adjusted accordingly. Research on healthcare environments has found that patients benefit from privacy (e.g., González-Santos, 2011), quietness (e.g., Hagerman et al, 2005), and the presence of family members (Blumberg & Devlin, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…very small proportion of the total number of hospitalized patients and they are underrepresented in the research on the quality of these services (Blumberg & Devlin, 2006;Jedeloo et al, 2010). Some studies conclude that the first step to improve adolescents' health-care experience is to ask them about their preferences (Britto et al, 2007).…”
mentioning
confidence: 99%
“…But the life expectancy of children with severe diseases has improved significantly, and the increase in the longevity of children with chronic diseases has led to an increase in the number of adolescents who suffer from such diseases and, consequently, an increase in the demand of hospital services for this section of the population (Alderman, Rieder, & Cohen, 2003). Despite this, adolescents represent a very small proportion of the total number of hospitalized patients, and they are underrepresented in the research on the quality of these services (Blumberg & Devlin, 2006;Jedeloo et al, 2010). Some studies conclude that the first step to improve adolescents' health care experience is to ask them about their preferences (Britto et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation